Functional biology of plants - Hodson, Martin J.; Bryant, John A. (Wiley-Blackwell, 2012)
Functional Biology of Plants provides students and researchers with a clearly written, well structured whole plant physiology text. Early in the text, it provides essential information on molecular and cellular processes so that the reader can understand how they are integrated into the development and function of the plant at whole-plant level